A study of temperate climate for comfort temperature predictions in natural ventilation buildings using Ashrae Rp-884 database - Tay, Lee Yong (2019)
Many studies addressed the effect of climate on thermal comfort by referring either to the developed climate world map designed by Kottek et al or by Peel et al method. However, they ignored the fact that each method may provide different results. Additionally no consideration was made in their studies by addressing the effect of climate subtypes on thermal comfort, the variation of climate over years on thermal comfort, and the variation of the monthly neutral temperatures over years due to climate variation. Hence, this research addressed the effect of the Koppen-Geiger climate classification systems on thermal comfort of various locations subjected to climate type C. The ASHRAE RP-884 database was used in the investigation. At the initial stage, Kottek and Peel climatic world maps of Koppen-Geiger, and the New LocClim 1.10 software were used for the identification of main climate types. Ten survey sites subjected to climate type C were identified. In the next stage, three locations were further selected for the identification of main and subtypes climate over a period of 35 years (1980-2014). The Kottek and Peel versions of Koppen-Geiger climate classification were used. A comparison was made by considering short-versus long-term climate types. In the final stage, the dominant long-term, the average long-term, and the short-term neutral temperatures were predicted and analysed according to main and sub-climate types. The analysed results revealed that shifts in climate types did not necessarily affect the predicted indoor neutral temperatures. It was also observed that the neutral temperature, when determined using the thermal comfort survey conducted in a year or in a few months, was also subjected to variation. The Koppen-Geiger approach seems not to be an appropriate method for predicting and monitoring the effect of climate variation and change on humans' thermal comfort. It cannot be used to investigate the impact of relative humidity on thermal comfort.